Winning elections in the 21st century - Simpson, Dick W.; O'Shaughnessy, Betty (University Press of Kansas, 2016)
"This how-to book on winning elections in the current environment saturated with new forms of communication--written by coauthors who possess both academic training in political science and practical experience gained from being former elected officials--uses examples from presidential and congressional campaigns, but focuses on guidance most applicable to the half million-plus races for local and state government elected offices that occur every six years in the U.S. As such, its greatest utility will be to the candidates and their staff, as well as in the college classrooms that focus on the practices culminating on election days throughout America. In addition to explaining how campaigns are really run, the authors raise fundamental questions about their impact on citizen participation and democracy itself"--